Penetapan Selat Lombok Sebagai Particulary Sensitive Sea Area (PSSA) Dalam Kerangka Perlindungan Ekosistem Laut Indonesia - Atalo, Rainhard Florian (Ranah Research : Journal of Multidisciplinary Research and Development, 2025)
Indonesia, as an archipelagic country, has a vast maritime area, making it a significant route for international shipping. One of the essential regulations in managing Indonesia's waters is the establishment of the Indonesian Archipelagic Sea Lanes (ALKI), aimed at regulating foreign ship passage rights. This study focuses on Indonesia's efforts to designate the Lombok Strait as a Particularly Sensitive Sea Area (PSSA) to protect the marine ecosystem and biodiversity in the region. The research employs a normative legal research method with a statute-based approach, analyzing both national and international regulations related to marine protection, such as UNCLOS, MARPOL, and SOLAS. The study's findings indicate that the PSSA designation in the Lombok Strait aims not only to preserve the environment but also to support the economic sustainability dependent on the region, such as tourism and fisheries. Additionally, the challenges in implementing this policy include coordination among countries and compliance with existing international regulations